Model Kooperatif Tipe TGT Bantuan Media Bamboozle dalam Meningkatkan Hasil Belajar Peserta Didik SMK Kelas XI ATPH Materi Identifikasi Pupuk - Fiska Noviandana; Sukian Wilujeng; Maureen Evita (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to improve student learning outcomes in Grade XI ATPH 3 of SMK Negeri 1 Purwosari in the subject of Vocational Expertise Concentration on fertilization elements by implementing the cooperative learning model type Teams Games Tournament (TGT) using the interactive media Bamboozle. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through learning outcome tests, observation, and documentation. The results showed that the implementation of the TGT model supported by Bamboozle media improved students’ average scores from 54.55 in the pre-cycle to 72.73 in cycle I and 81.82 in cycle II. The percentage of mastery learning increased from 6% to 39% and then to 82%. The use of TGT combined with Bamboozle was proven effective in enhancing students’ learning outcomes, engagement, and motivation. Thus, this strategy is recommended as an alternative interactive and engaging learning method in vocational subjects at vocational schools.